PERBEDAAN PRESTASI BELAJAR FISIKA ANTARA SISWA YANG BERASAL DARI SMP DAN MTS PADA MADRASAH ALIYAH DARUSSYARI’AH MESJID RAYA BAITURRAHMAN BANDA ACEH - Syarifah Rita Zahara (Jurnal Dedikasi Pendidikan, 2017)
This study aims to determine differences in student achievement of physics lessons. In this study, the instrument used is test, a series of questions in the form of questions that can be used to measure student achievement derived from SMP and MTs in Madrasah Aliyah Darussyari'ah Baiturrahman Mosque Banda Aceh. The test referred to in this study is a test in the field of physics studies. Test given in the form of objective test, the questions in the form of multiple choice and essay in accordance with the curriculum of the field of physics studies level Madrasah Aliyah class XII. Normality and homogenity test results indicate that the data is normally distributed and homogeneous. With a significant level α = 0.05, then from the chi-square table obtained X = ((0.95) (4)) ^ 2 = 9.49, since X_count ^ 2 <X_table ^ 2 is 6.765 <9.49. These results indicate that the value of physics learning achievement derived from SMP normal distribution. And for the MTs with a significant level of α = 0.05, then from the chi-square table obtained X = ((0.95) (4)) ^ 2 = 9.49, since X_count ^ 2 <〖X〗 _table ^ 2 is 5.358 <9.49. These results indicate that physics learning achievement derived from MTs is normally distributed. From the t distribution list with probability 0.95 and dk = 24, obtained = 0.71 = 1.71, then the calculation is obtained t = 3.20. Because t_count> t_ (table) is 3.20> 1.71, so obviously the price t is in the acceptance area of H_a. Thus Ho is rejected and Ha accepted at a significant level of 0.05, so there is a significant difference in physics learning achievement between students who come from junior and MTs acceptable.